Defining pharyngeal contractile integral during high-resolution manometry in neonates: a neuromotor marker of pharyngeal vigor. (September 2018) - Jadcherla, Sudarshan; Prabhakar, Varsha; Hasenstab, Kathryn; Nawaz, Saira; Das, Jayajit; Kern, Mark; Balasubramanian, Gokulakrishnan; Shaker, Reza
Abstract Background Pharyngeal contractility is critical for safe bolus propulsion. Pharyngeal contractile vigor can be measured by Pharyngeal Contractile Integral (PhCI): product of mean pharyngeal contractile amplitude, length, and duration. We characterized PhCI in neonates and examined the hypothesis that PhCI differs with mode of stimulation. Methods Nineteen neonates born at 38.6 (34–41) weeks gestation were evaluated at 42.9 (40.4–44.0) weeks postmenstrual age using high-resolution manometry (HRM). PhCI was calculated using: (a) Conventional and (b) Automated Swallow Detection algorithm (ASDA) methods. Contractility metrics of all pharyngeal regions were examined using mixed statistical models during spontaneous and adaptive state (pharyngeal and oral stimulus) swallowing. Results PhCI of oral stimuli swallows were distinct from pharyngeal stimuli and spontaneous swallows (P  < 0.05). Correlation between conventional and ASDA methods was high (P  < 0.001). PhCI increased with swallows for pharyngeal stimulation (P  < 0.05) but remained stable for swallows with oral stimulation. PhCI differed between proximal and distal pharynx (P  < 0.001). Conclusions PhCI is a novel reliable metric capable of distinguishing (1) proximal and distal pharyngeal activity, (2) effects of oral and pharyngeal stimulation, and (3) effects of prolonged stimulation. Changes in pharyngeal contractility with maturation, disease, and therapies can be examined with PhCI.